2020
DOI: 10.1523/jneurosci.2586-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Modulates Dynamic Decision-Making during Foraging

Abstract: The mesolimbic dopaminergic system exerts a crucial influence on incentive processing. However, the contribution of dopamine in dynamic, ecological situations where reward rates vary, and decisions evolve over time, remains unclear. In such circumstances, current (foreground) reward accrual needs to be compared continuously with potential rewards that could be obtained by traveling elsewhere (background reward rate), to determine the opportunity cost of staying versus leaving. We hypothesized that dopamine spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
63
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 53 publications
(81 reference statements)
16
63
0
Order By: Relevance
“…Third, the experiment could be limited in its trial-based structure. While some patch-leaving designs are trial-based (Barack et al, 2017; Constantino & Daw, 2015; Kane et al, 2017; Hayden et al, 2011), studies tend to compute reward rates (Kane et al, 2017; Lottem et al, 2018), the probability of leaving (Constantino & Daw, 2015) or leaving times (Barack et al, 2017; Hayden et al, 2011; Le Heron et al, 2020; Lottem et al, 2018) using some continuous time information, such as the number of seconds in a patch. In the present experiment, we used trial-wise data to model discrete choice behaviour based on a previous computational model (Constantino & Daw, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the experiment could be limited in its trial-based structure. While some patch-leaving designs are trial-based (Barack et al, 2017; Constantino & Daw, 2015; Kane et al, 2017; Hayden et al, 2011), studies tend to compute reward rates (Kane et al, 2017; Lottem et al, 2018), the probability of leaving (Constantino & Daw, 2015) or leaving times (Barack et al, 2017; Hayden et al, 2011; Le Heron et al, 2020; Lottem et al, 2018) using some continuous time information, such as the number of seconds in a patch. In the present experiment, we used trial-wise data to model discrete choice behaviour based on a previous computational model (Constantino & Daw, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This results in a simple optimal policy called the Marginal Value Theorem (MVT, Charnov, 1976), wherein animals should leave their current option when its reward falls below the average reward rate for the environment. Empirical studies have shown that leave decisions in mice, rats, monkeys and humans are consistent with this decision rule (Constantino & Daw, 2015, Hayden et al, 2011; Kane et al, 2017; Le Heron et al, 2020; Lottem et al 2018). Evidence has also suggested that the unique structure of foraging decisions might be solved using neural substrates that are at least partially distinct from those involved in other reward-based decisions (Kolling et al, 2012; Rushworth et al, 2011), with the anterior cingulate cortex serving a critical role in regulating decisions about whether to disengage from an option (Fouragnan et al, 2019; Hayden et al, 2011; Wittmann et al, 2016, see Kolling et al, 2016; Mobbs et al, 2018; Rushworth et al, 2011 for reviews).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Newer evidence has suggested that subcortical areas and especially those implicated in dopaminergic transmission have a more substantial role in explore-exploit behavior than previously realized (Chakroun et al, 2020). Increased dopamine in the striatum promoted explorative behavior (Verharen et al, 2019), influenced participants to leave patches in poor environments earlier in a foraging task (Heron et al, 2020), attenuated directed exploration, and lowered representations of overall uncertainty in the insula and dACC (Chakroun et al, 2020). However, a major factor in explore-exploit decisions is the environmental uncertainty of new options (Badre et al, 2012;Navarro et al, 2016;Tomov et al, 2020), information which seems to be largely processed in the PFC.…”
Section: The Explore-exploit Dilemmamentioning
confidence: 98%
“…In their recent study, Le Heron et al (2020) fill this gap by investigating how these decisions are causally affected by dopaminergic state in an ecologically valid foraging scenario. In their study, participants could choose between collecting reward (milk filling a bucket) at one location (patch) or leaving for another patch which incurred a cost in the form of a fixed travel time.…”
mentioning
confidence: 99%